A real-time tracking controller for piezoelectric actuators based on reinforcement learning and inverse compensation. (June 2021) - Qin, Shijie; Cheng, Long
Abstract: Nanotechnology is a promising technology and has been widely applied for sustainable smart cities. As the fundamental devices for nanotechnology, piezoelectric actuators (PEAs) have gained wide attention in precision manufacturing because of the advantages of rapid response, large mechanical force and high resolution. However, the inherent nonlinearities of PEAs hinder wide applications for nano-positioning and high-precision manipulation. To eliminate these nonlinearities, various control methods have been proposed, while the optimal control of PEAs is considered rarely. Inspired by the reinforcement learning, adaptive dynamic programming (ADP) is proposed to solve the optimal tracking control problem of PEAs. In this paper, a controller based on reinforcement learning and inverse compensation is designed for the tracking control of PEAs. The experiments on the PEA platform are designed to verify the effectiveness of the proposed method. Comparisons with some representative controllers have demonstrated that the proposed controller has a better control performance. Highlights: Reinforcement learning first applied for controlling of piezoelectric actuators. Inversion-based tracking controller designed with the hysteresis compensator. High-precision real-time tracking control of piezoelectric actuators.